KEADAAN PSIKOLOGIS ANAK UMUR DINI (RISET PERTUMBUHAN KEAGAMAAN PADA TAMAN PENITIPAN ANAK PINANG SEBATANG) - Hardianti, Tuti; Irwansyah, Irwansyah; Aswir, Aswir; Herawati, Mimi (Institut Agama Islam Syekh Maulana Qori Bangko, 2024)
There are 2 cases discussed in this article, namely: (1) What is the psychological condition that occurs in children at the Permata Child Care Center (TPA) Pinang Sebatang, (2) How is the religious development of children at the Pinang Sebatang Child Care Center (TPA). The aim of this research is to identify the psychological condition and religious growth of children at the Pinang Sebatang Child Care Center (TPA), Bangko City. To uncover this case in depth and comprehensively, researchers used qualitative descriptive methods which are useful for sharing data, facts and information regarding the psychological condition of children and the religious development of children in that place, after which the information is described, analyzed and discussed to reveal the case. From the research results, it was found that (1) the psychological condition of children in the Pinang Sebatang TPA has a psychological condition (normal) or the child has been able to adapt and relate well to the Pinang Sebatang TPA area for children with psychological problems. The condition of children (not normal) has a tendency to cry easily, get angry easily, feel insecure and unable to adapt to the area, (2) The religious growth of children at Pinang Sebatang TPA found 2 types of religious growth, firstly children easily accept the educational process and description. For example, in the process of learning to perform ablution, prayer, and learning to recite the Koran, children can receive education regarding these interpretations well. Second, it is difficult for children to receive religious education in the sense that there are children who have difficulty learning to read, learning to memorize and are unable to master what is being taught and are not yet able to model what is taught by their supervising teacher.